Complement Receptor Type 1 (CR1, CD35), the Inhibitor of BCR-Mediated Human B Cell Activation, Differentially Regulates TLR7, and TLR9 Induced Responses - Mácsik-Valent, Bernadett; Nagy, Katinka; Fazekas, László; Erdei, Anna (Frontiers in Immunology, 2019)
The complement system and Toll-like receptors (TLRs) are essential contributors of innate immunity. Separate activation of these systems has been shown to play a role in initiating and shaping the adaptive immune response, however the modulation of various B cell functions by the simultaneous involvement of these two systems has not yet been uncovered. We demonstrate here that occupancy of complement receptor type 1 (CR1, CD35) by its natural, complement component C3-derived ligand significantly and dose dependently reduces the TLR9-induced expression of activation markers, cytokine production, proliferation, and antibody production by human B cells, but has no effect on the TLR7-induced functions. The synergistic response to the simultaneous engagement of either TLR9 or TLR7 along with the BCR however, is significantly inhibited by CR1 occupancy. Our findings imply that both under physiological and pathological conditions, when complement- and TLR-activating microbial and damage products are present in the B cell environment, the cooperation between CR1 and TLR7 or TLR9 provides additional levels of the regulation of human B cell functions.